English Class Scheduling Information System at Indonesian-American Educational Institutions - Bajsair, Faik; Baisyir, Fauzi; Pranoto, Gatot Tri ((JAIS) Journal of Applied Intelligent System, 2024)
The purpose of the research is to create and implement a simple class scheduling application that is useful to minimize the occurrence of clashes of time, classes, levels, teachers and students at the same time. The research method used is the Descriptive Method with the type of case study research. The descriptive method is a method of researching the status of a group of people, an object, a set of conditions, a system of thought or an event in the present. From this Thesis or Final Project, the author can draw the conclusion that the English Class Scheduling Information System in Indonesian-American Educational Institutions is more effective, fast, conceptual, and up to date in data processing